Formalisation method for the text expressed knowledge - Jakupović, Alen (Array, 2014)
This paper describes a method of knowledge representation as a set of text expressed statements. The method is based on the identification of word-categories/phrases and their semantic relationships within the observed statement. Furthermore, the identification of semantic relationships between words/phrases using wh-questions that clarify the role of the word/phrase in the relationship is described. A conceptual model of the computer system based on the formalization method of text-expressed knowledge is proposed. The subsystem text formalization is described in detail, especially its parts: syntactic analysis of the sentence, sentence formalization, phrase structure grammar and lexicon. The phrase structure grammar is formed by induction and it is used to generate the language of the formalized notation of a sentence. The derivation of grammar is based on the simple phrase structure grammar which was used for the syntactical analysis of informal language notation. In its base, the suggested method translates sentences of the informal language into formal language sentences which are generated by the derivated phrase structure grammar. Current limitations of the method that also set the path of its further development are shown. Next concrete steps in the development of the method are also described.